The effect of incorporating Tulsi (Ocimum sanctum) into fish feed on the hematological parameters, growth, and survival rates of Labeo rohita (fingerlings). - Shrutika S. Kurhekar; Dr. Y. D. Akhare (The Bioscan, 2025)
Natural immunosuppressants are compounds that can assist modulate or suppress the immune system; they are produced from plants, herbs, or other natural sources. Medicinal herbs are increasingly being used in aquaculture for their natural immunostimulants and growth-promoting properties. The plant Tulsi, often called holy basil (Ocimum sanctum), is widely used in traditional medicine, particularly in Ayurveda, because of its ability of anti-inflammatory, antibacterial, and immunomodulatory qualities. Diets containing O. sanctum at various levels, such as 200mg, 400mg, and 600mg, were utilized as test diets, whereas diet lacking O. sanctum served as the control tank (C). The experiment lasted 60 days, during which time the water quality was monitored every other day. The results showed that the innate immune response was improved when Ocimum sanctum was administered through different diets, primarily in T1, T2, and T3 diets. This boosted the total erythrocyte count, hemoglobin, and total leukocyte count. Over the course of the 60-day trial, growth and hematological markers were examined every 20 days. After 20 days, 40 days, and 60 days, the first, second, and final readings were taken. The current study was carried out to investigate the influence of dietary Tulsi extract on fingerlings of L. rohita’s growth, survival, and hematological levels.